Furfural oxidation to maleic acid with H2O2 by using vanadyl pyrophosphate and zirconium pyrophosphate supported on well-ordered mesoporous KIT-6. Issue 1 (February 2019) - Rezaei, Masoume; Najafi Chermahini, Alireza; Dabbagh, Hossein A.; Saraji, Mohammad; Shahvar, Ali
Graphical abstract: Abstract: The improvement of catalytic technology in oxidation of organic compounds especially renewable resources to value-added compounds is currently extended. In this work, the well-ordered mesoporous structure of KIT-6 was synthesized. Then, a mixture of vanadyl pyrophosphate and zirconium pyrophosphate was successfully stabilized on KIT-6 scaffold and characterized using XRD, N2 adsorption/desorption, SEM/ EDX/ elemental mapping, TEM, ICP-AES, FT-IR and Raman spectroscopic techniques. The activity of catalysts was examined on the oxidation reaction of furfural to maleic acid using H2 O2 . In order to improve the reaction conditions and maleic acid yield over vanadium and zirconium supported on KIT-6, furfural oxidation was performed in the presence of 0.25 Zr/V ratio-loading at 70 °C with 3:1 (H2 O2 : furfural mole ratio), in acetonitrile as the solvent. Under these reaction conditions, 81.2% furfural conversion and 29.2% maleic acid yield were observed after one hour reaction time. Finally, the stability and reusability of the catalysts were evaluated in several consecutive times under optimum reaction conditions.